Prognostic Significance of miRNA Subtypes in Melanoma: A Survival Analysis and Correlation with Treatment Response Across Patient Stages - Mihaela Prodan; Alis Dema; Bianca Roxana Nataras; Edward Seclaman; Vlad Bloanca; Zorin Crainiceanu; Ilona Emoke Deak; Claudia Raluca Balasa Virzob; Ana-Olivia Toma; Roxana Manuela Fericean (Biomedicines)
Background and Objectives: Melanoma remains a leading cause of skin cancer mortality despite advancements in targeted therapies and immunotherapies. MicroRNAs (miRNAs) have emerged as potential biomarkers for cancer prognosis and treatment response. This study aims to analyze survival outcomes according to various miRNA subtypes, assess the association between specific miRNAs and treatment response, and include patient staging to evaluate their prognostic significance. Methods: A retrospective cohort study was conducted on 90 patients from the Pius Brinzeu County Emergency Clinical Hospital, Timisoara, between 2019 and 2022. The cohort included 45 patients with advanced-stage melanoma and 45 with benign nevi. miRNA expression levels were quantified using the miRNeasy Kit and the Human Cancer PathwayFinder miScript miRNA PCR Array. Survival analysis was performed using the Kaplan–Meier method, and Cox proportional hazards models were used to assess the impact of miRNA expression on survival. Logistic regression analyzed the association between miRNA markers and treatment response, adjusting for patient staging. Results: Elevated levels of hsa-miR-200a-3p and hsa-miR-335-5p were significantly associated with poorer overall survival (p < 0.01), particularly in stage III and IV patients. Conversely, higher expression of hsa-miR-451a correlated with improved survival rates (p = 0.02). Patients with increased hsa-miR-29b-3p expression showed a better response to immunotherapy (OR = 2.35, 95% CI: 1.15–4.79). Multivariate analysis confirmed that miRNA expression levels and patient staging were independent predictors of survival and treatment response. Conclusions: Specific miRNA subtypes are significant prognostic markers in melanoma, influencing survival outcomes and treatment responses across different patient stages. Incorporating miRNA profiling into clinical practice could enhance personalized treatment strategies and improve patient prognoses.